The efficacy and safety of intralesional immunotherapy with measles, mumps, rubella virus vaccine for the treatment of common warts in adults - Pushpinder Singh Chauhan; Vikram K Mahajan; Karaninder Singh Mehta; Ritu Rawat; Vikas Sharma (Wolters Kluwer Medknow Publications, 2019)
Background: Most therapeutic modalities for common warts remain unsatisfactory. Objectives: To evaluate efficacy and safety of intralesional MMR (measles, mumps, rubella virus) vaccine in the treatment of common warts in adults. Patients and Methods: There were 110 (M:F = 61:49) patients aged 19-62 years having 1-211 warts over dorsal hands, feet, palms, soles, and periungual skin for 1-252 months. MMR vaccine 0.25 mL was injected intralesionally in the largest wart and repeated at 2-week interval until complete clearance or maximum of five doses. The outcome was evaluated as complete clearance, excellent, good, or unsatisfactory response on visual analog scale at every visit and at 4 and 8 weeks, thereafter by comparing baseline clinical photograph. Likert scale was used for patient satisfaction level assessment similarly. Results: Only 51 patients completed the study and 42 (82.4%) of them showed complete clearance of warts and 9 (17.6%) patients showed good or unsatisfactory response. In 4 (7.8%) patients, the warts subsided completely after one dose itself. The four patients showing excellent response after five doses initially also continued to improve during follow-up period of 8 weeks. Except for injection site pain, no adverse effects were noted. There was no recurrence of warts among cured who were also very much satisfied from treatment. Conclusion: Despite variable results, intralesional MMR vaccine immunotherapy appears another possible safe and effective treatment option for common warts in a set of adult patients with advantages of regression of distant warts, no significant adverse effects and low recurrence. However, well-designed, controlled studies for minimum effective dose and treatment schedule are highly desirable to make any recommendation.